(untitled) (Scientific journal of the Fergana State University, 2023)
The article deals with the policy of public administration during the development of new Uzbekistan, raising the issue of women leaders to the level of public administration policy, their rights to appoint, elect and be elected to administrative positions, the manifestation of women’s activity in governance, their activities as active members of society, career issues, as well as various artificial barriers to the principles of equality in management, work in a team as a whole, that is, the question of the inextricable connection with social stereotypes is raised.